Impact of cavity location on base pressure at Supersonic Mach 1.8 - Ridwan, R; Muhamad Zuraidi, Nur Husnina; Khan, Sher Afghan (The Scientific Press, 2022)
In this day and age, researchers and engineers are actively exploring research in the supersonic Mach number flow field, primarily related to the base pressure of aerospace vehicles and nozzle variants. The boundary layer theory explained the flow separation caused by fluid motion. The turbulent boundary layer at the base will generate supersonic expansion flow in the recirculation zone, resulting in a pressure decrease at the base region and a free viscous layer from the base region towards the free stream direction. Several experimental studies on base pressure and flow development have been conducted with sudden expansion. Base pressure is affected by the geometry of the passage, the area ratio, and the L/D ratio. Numerical simulation simulates the flow from a Converging Diverging nozzle that has suddenly expanded into an enlarged duct with a cavity. The Mach number for this study is 1.8, and the area ratio is 2.56. The L/D ratio considered was from 1 to 10. The nozzle pressure ratio and aspect ratio of the cavity were considered in this study. The study investigates the impact of cavity location from the base wall toward the base pressure using Computational Fluid Dynamics. The simulated nozzle pressure ratio was for over, under, and ideally expanded cases. The results show that the NPR and cavity location from the base wall strongly influenced the base pressure.